Removal of organic contaminants from wastewater with GO/MOFs composites. - Fuhua Wei; Huan Zhang; Qinhui Ren; Hongliang Chen; Lili Yang; Bo Ding; Mengjie Yu; Zhao Liang (PLoS ONE)
Graphene oxide/metal-organic frameworks (GO/MOFs) have been prepared via solvothermal synthesis with ferrous sulfate heptahydrate, zirconium acetate and terephthalic acid for the purpose of removing organic pollutants from wastewater. The composites were analyzed using scanning electron microscopy, infrared spectrometry, and XRD. Tetracycline hydrochloride and orange II were implemented as model pollutants to evaluate the efficacy of the GO/MOFs in water purification, in which 50 mg of Zr/Fe-MOFs/GO was mixed with 100 mL of 10 mg/L, 20 mg/L, 30 mg/L, or 50 mg/L tetracycline hydrochloride solution and 25 mg/L, 35 mg/L, 45 mg/L, or 60 mg/L orange II solution, respectively. The removal efficacy after 4 hours was determined to be 96.1%, 75.8%, 55.4%, and 30.1%, and 98.8%, 91.9%, 71.1%, and 66.2%, respectively. The kinetics of pollutant removal was investigated for both tetracycline hydrochloride and orange II and excellent correlation coefficients of greater than 0.99 were obtained. The high efficacy of these MOFs in pollutant removal, coupled with their inexpensive preparation indicates the feasibility of their implementation in strategies for treating waste liquid. As such, it is anticipated that Zr/Fe-MOFs/GO composites will be widely applied in wastewater purification.